Complete Nucleotide Sequences of mcr-4.3-Carrying Plasmids in Acinetobacter baumannii Sequence Type 345 of Human and Food Origin from the Czech Republic, the First Case in Europe - Bitar, Ibrahim; Medvecky, Matej; Gelbicova, Tereza; Jakubu, Vladislav; Hrabak, Jaroslav; Zemlickova, Helena; Karpiskova, Renata; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2019)
Here, we describe two plasmids carrying mcr-4.3 in two Acinetobacter baumannii strains isolated from imported food and a clinical sample. The comparative analysis of these plasmids, with two other plasmids reported in the NCBI database, highlighted the common origin of the plasmidic structure carrying mcr-4.3 This is the first case of the mcr-4.3 gene in a A. baumannii strain isolated from a clinical case in Europe. We hypothesize that food import is initiating the spread in Czech Republic.
Keywords: Microbial Sensitivity Tests; Humans; WGS; Female; mikrobiální testy citlivosti; lidé; plazmidy; Europe; peptidy; Peptides; colistin resistance; Acinetobacter baumannii; ženské pohlaví; Drug Resistance, Bacterial; mcr-4.3; Czech Republic; Aged, 80 and over; senioři nad 80 let; bakteriální léková rezistence; Česká republika; Plasmids; Evropa